Leaflets and continual educational offerings led to increased coverage rate of newborn hearing screening in Akita. Issue 4 (August 2018) - Sato, Teruyuki; Nakazawa, Misao; Takahashi, Shin; Mizuno, Tomomi; Sato, Akira; Noguchi, Atsuko; Sato, Megumi; Katagiri, Sadako; Yamada, Takechiyo
Abstract: Objective: Newborn hearing screening (NHS) has been actively performed in Japan since 2001. The NHS coverage rate has increased each year in Akita Prefecture. We analyzed the details of the NHS program and how the Akita leaflets and the many educational offerings about the importance of NHS led to the high NHS coverage rate. Methods: A retrospective study was conducted in liveborn newborns in hospitals and in clinics where hearing screening was performed from the program's beginning in 2001 through the end of 2015. We describe the chronological history of NHS. The outcome data of NHS were collected from our department and analyzed. Results: From the founding of the program in 2001 to 2015, the live birth rate in Akita continually declined. Nevertheless, the number of infants receiving NHS rose each year. Since 2012, the coverage rate of NHS has been over 90%. From 2001 to 2015, 75, 331 newborns constituted the eligible population for the NHS program. Since 2012, the number of NHS tests has stabilized. We prepared educational leaflets for Akita Prefecture early in 2002. We also provided many educational classes about the importance of NHS for not only pregnant women but also professionals including obstetricians and gynecologists, pediatricians and municipal staff members. The NHS program received the complete endorsement of the Akita Association of Obstetricians and Gynecologists in 2010. The largest increase in the NHS coverage rate occurred from 2001 to 2002, and the second largest increase occurred from 2009 to 2010. The number of participating institutions increased the coverage rate. The coverage rate is strongly correlated with the number of participating institutions (rs = 0.843, p <  0.001, Spearman's rank correlation coefficient). Comparing the coverage rate for 5 years before and after the Akita Association of Obstetricians and Gynecologists reached their consensus on the importance of NHS, the coverage rate after 2010 was significantly higher than before 2010 ( p  < 0.001, paired sample t-test). Conclusion: The NHS coverage rate ultimately reached 95.4% without need for legislation or subsidization. The number of participating institutions increased each year, and the number of NHS tests and the coverage rate increased proportionately. The number of participating institutions statistically has a strong correlation with the number of NHS tests and the coverage rate. Our research indicates that the Akita leaflets and the provision of educational sessions about the importance of NHS were the most significant factors in establishing the high NHS coverage rate.